Dream sharing frequency: associations with sociodemographic variables and attitudes toward dreams in an american sample - Schredl, Michael; Bulkeley, Kelly (Dreaming, 2019)
Dreaming is a personal experience during sleep that can, for various reasons, be shared upon awakening with other people. A sample of 5,255 American adults with diverse sociodemographic and ethnic backgrounds completed an online survey including an item eliciting the frequency of dream sharing. According to these data, dream sharing is fairly common among the general population—23% of the sample reported sharing dreams at least once a week. However, the practice is not universal, as 24% of the sample reported never sharing their dreams. The frequency of dream sharing was affected by a variety of factors such as age, gender, dream recall frequency, attitude toward dreams, education, relationship status, and ethnicity. As this is the first quantitative study reporting cultural differences in dream sharing frequency (e.g., Hispanics share their dreams more often than Whites), it would be very interesting to carry out surveys in different countries to study cultural effects on dream recall frequency and other dream variables. (PsycINFO Database Record (c) 2019 APA, all rights reserved)
Gesehen am 31.10.2019